Optimizing Early Detection of Bhabinkamtibmas Polres Pekalongan to Prevent the Criminal Act of Theft by Weighting in the Context of ‘Presisi Polri’ - Adira Rizky Nugroho (Indonesian Journal of Police Studies, 2022)
The Corona Virus Disease 2019 (Covid-19) pandemic has affected not only the health sector, but also the economic sector. This condition causes changes in people's lives; on the one hand, people's needs increase, while their financial income decreases. This inequality has the potential to create crime vulnerabilities, one of which is the criminal act of theft by weighting experienced by the community under the jurisdiction of the Polres Pekalongan (District or Municipality Police). Cases of theft by weighting dominated other criminal cases at the Polres Pekalongan (District Police) from 2018 to 2021. Repressive efforts to combat the criminal act of theft by weighting seem not yet effective enough, so that preventive efforts are needed against the criminal act of theft by weighting through early detection activities. The National Police as a public servant strives to maintain the security and order situation in the community through the Community Policing function and the “Presisi Polri” concept. Therefore, Bhabinkamtibmas as the front guard carrying out the function of Polmas (Community Policing) is essential to preventing the criminal act of theft by weighting through the implementation of early detection. The study aims to determine the feasibility implementation in early detection of Bhabinkamtibmas of the Polres Pekalongan (District Police) for the prevention of theft by weighting in the context of a “Presisi Polri”. This research is qualitative research with a case study approach where data collection is done through interviews, observations, document studies, and focus group discussions (FGD) to a number of sources in the jurisdiction of the Pekalongan Police. The results of this study indicate that Bhabinkamtibmas needs to optimize its early detection ability through observation activities, seeking information and willingness to listen actively to map the security and security situation in its area of ​​duty. This is in line with the “Presisi Polri” Transformation, particularly in the fifth program, namely Strengthening the performance of Kamtibmas Maintenance through predictive policing activities.